2021
DOI: 10.1002/clc.23758
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of subclavian vein to inferior vena cava collapsibility by ultrasound in acute heart failure: A pilot study

Abstract: Background: Management of acute decompensated heart failure (ADHF) requires accurate assessment of relative intravascular volume, which may be technically challenging. Inferior vena cava (IVC) collapsibility with respiration reflects intravascular volume and right atrial pressure (RAP). Subclavian vein (SCV) collapsibility may provide an alternative. Hypothesis:The purpose of this study was to examine the relationship between SCV collapsibility index (CI) and IVC CI in ADHF.Methods: This was a prospective stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…19,20 Although there is a growing need of a noninvasive tool to accomplish correct fluid management, the available methods are still nonoptimal, expensive and require long procedures and highly specialized personnel, so less invasive techniques such as respiratory CI of IVC with its' prompt identification of intravascular volume in critically ill patient especially in ED has been implemented in clinical use. 10,[21][22][23][24][25][26] Although our study supports previous studies, it primarily investigated an unstudied topic, that is, the relationship between IVC CI measurement and volume status in patients with hyponatremia. Thus, unlike its predecessors, the present study may provide guidance in hyponatremia management (Figure 4).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…19,20 Although there is a growing need of a noninvasive tool to accomplish correct fluid management, the available methods are still nonoptimal, expensive and require long procedures and highly specialized personnel, so less invasive techniques such as respiratory CI of IVC with its' prompt identification of intravascular volume in critically ill patient especially in ED has been implemented in clinical use. 10,[21][22][23][24][25][26] Although our study supports previous studies, it primarily investigated an unstudied topic, that is, the relationship between IVC CI measurement and volume status in patients with hyponatremia. Thus, unlike its predecessors, the present study may provide guidance in hyponatremia management (Figure 4).…”
Section: Discussionsupporting
confidence: 81%
“…The absence of methods that directly measure body volume status, with the paramount importance to accurately assess volume status in patients presenting to ED, necessitated the development of indirect measurement methods; such as the dilution techniques for the body fluids assessment, energy X‐ray absorptiometry, underwater weighing, air displacement plethysmography, bioelectrical impedance analysis, magnetic resonance, and computed tomography 19,20 . Although there is a growing need of a noninvasive tool to accomplish correct fluid management, the available methods are still nonoptimal, expensive and require long procedures and highly specialized personnel, so less invasive techniques such as respiratory CI of IVC with its' prompt identification of intravascular volume in critically ill patient especially in ED has been implemented in clinical use 10,21–26 …”
Section: Discussionmentioning
confidence: 99%
“…Respiratory variations of the subclavian/proximal axillary vein (SCV) and internal jugular vein (IJV) are highly position dependent, as is jugular venous distension, and should be performed at a 30–45 degree upper body incline [ 45 ]. SCV CI and IJV CI do not appear to be affected by intra-abdominal hypertension or positive end-expiratory pressure [ 46 , 47 ].…”
Section: Comparison Of Techniques To Assess Intravascular Volume or R...mentioning
confidence: 99%
“…In 120 patients undergoing general anesthesia, a cut-off of 36% for SCV CI with deep breathing (presumably without head elevation) predicted post-induction hypotension in 42% of patients (sensitivity 90%, specificity 87%), similar to performance of IVC CI using a cut-off of 37% (sensitivity 94%, specificity 84%) [ 43 ]. Comparison of cut-off values for the SCV CI to predict IVC CI cut-off at 30–45 degrees supine without deep breathing from four studies are shown in Table 5 [ 45 , 48 , 50 , 51 ].…”
Section: Comparison Of Techniques To Assess Intravascular Volume or R...mentioning
confidence: 99%
See 1 more Smart Citation